1984
DOI: 10.1111/j.1471-4159.1984.tb05413.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Rates in Rats with Portacaval Shunts

Abstract: Protein synthesis rates were measured (33 days postoperatively) in rats with portacaval shunts and in unoperated controls. In brain, no change in the rate of protein synthesis was evident in shunted rats. These data thus do not support the hypothesis that an inhibition of brain protein synthesis is a factor in the etiology of hepatic encephalopathy. The synthesis rate in forebrain at 82 days of age was 0.52%/h. Though brain wet weight was the same in both groups, rats with shunts grew relatively slowly, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…These findings are consistent with studies in isolated, intact hippocampus from adult mice showing that extracellular glutamate was oxidized in greater amounts with increasing concentration, and glutamate reduced oxidation of glucose (Dunlop et al, 1984). Recently, the glutamate transporter was shown to form multi-enzyme complexes with glycolytic enzymes and mitochondria that facilitate oxidation of very low levels (8 μmol/L) of glutamate as it is transported into the astrocytes (Genda et al, 2011; Bauer et al, 2012).…”
Section: Glutamate Is An Important Astrocytic Energy Sourcesupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with studies in isolated, intact hippocampus from adult mice showing that extracellular glutamate was oxidized in greater amounts with increasing concentration, and glutamate reduced oxidation of glucose (Dunlop et al, 1984). Recently, the glutamate transporter was shown to form multi-enzyme complexes with glycolytic enzymes and mitochondria that facilitate oxidation of very low levels (8 μmol/L) of glutamate as it is transported into the astrocytes (Genda et al, 2011; Bauer et al, 2012).…”
Section: Glutamate Is An Important Astrocytic Energy Sourcesupporting
confidence: 90%
“…Because astrocytes have much greater glutamate oxidative rates than GABAergic neurons and the corresponding rates in glutamatergic neurons were negligible, glutamate degradation is predominantly astrocytic (Hertz et al, 1988; Waagepetersen et al, 2002). The conclusion that glutamate is an important energy substrate for astrocytes is strongly supported by (i) the glucose-sparing actions of extracellular glutamate in cultured astrocytes (Swanson et al, 1990; Yu et al, 1992; Peng et al, 2001; Qu et al, 2001) and in isolated, intact hippocampus from adult mice (Dunlop et al, 1984), (ii) robust stimulation of astrocytic respiration by glutamate (Eriksson et al, 1995), and (iii) similar rates of astrocytic oxygen consumption with either glucose or glutamate as sole substrate (Hertz and Hertz, 2003). Under steady state conditions, oxidation of glutamate and GABA approximates the anaplerotic rate, which is ~15% of the total pyruvate oxidation rate (Hertz, 2011; Rothman et al, 2011), and glutamate synthesis and degradation in astrocytes produces nearly as much ATP as direct oxidation of glucose (Hertz et al, 1999; Hertz et al, 2007).…”
Section: Glutamate Is An Important Astrocytic Energy Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Construction of a portacaval anastomosis alone induces, besides portasystemic shunting of gut derived blood, a relative and absolute reduction of liver mass. 15-17 37 Urea synthesis capacity is limited in portacaval shunted rats, probably related to the reduced liver mass. '5"6 To these effects of portacaval anastomosis alone, the effects of chronic bile duct ligation were added.…”
Section: Discussionmentioning
confidence: 99%
“…129 In contrast, another study in PCA rats showed no difference in the rate of protein synthesis in different organs. 130 An increased skeletal muscle proteolysis mediated by the ubiquitin proteasome pathway has been described in the bile duct ligated rat. 131 However, the bile duct ligated rat as a model of cirrhosis differs from human cirrhosis because secondary biliary cirrhosis in humans is extremely rare and steatorrhea and malabsorption that accompany this procedure affect the muscle mass independent of cirrhosis.…”
Section: Pathogenesis and Mechanisms Of Sarcopenia In Cirrhosismentioning
confidence: 99%